Post-harvest indexes and colour parameters from arugula–beet intercropping under green manuring and population density - Abel da Silva Lino, Vitor; Bezerra Neto, Francisco; Cabral dos Santos, Elizângela; Medeiros Guerra, Natan; Karla Kelly da Silva Lino, Francisca; Paloma Pinheiro da Silva, Jéssica (Revista Ciência Agronômica, 2023)
In this study, the objective was to determine the post-harvest indexes of arugula leaves and beet roots in intercroppingunder a biomass mixture of diff erent green manures at diverse arugula population densities in two cropping seasons in a semi-aridenvironment. The experimental design was a randomised complete block design, with treatments arranged in a 4 × 4 factorial schemewith four replications. Treatments consisted of the combination of equitable amounts of Merremia aegyptia and Calotropis procerabiomass (20, 35, 50 and 65 t ha−1on a dry basis) and arugula population densities (400,000, 600,000, 800,000 and 1,000,000 plants ha−1).The characteristics evaluated in the arugula culture were titratable acidity, pH, and soluble solid and total soluble sugar content. Inthe beet crop, the same characteristics were evaluated in arugula, in addition to the betalain concentration and the internal colourparameters of the tuberose roots. Arugula showed the best post-harvest indexes when fertilised with green manure biomass amountsof 20, 20 and 65 t ha−1at a population density of 1,000,000 plants ha−1, while beet showed the best indices with green manureamounts of 65, 41, 36 and 40 t ha−1with an arugula density of 1,000,000 plants ha−1. The best colour parameters of beet roots wereobtained with green manure amounts of 30 and 32 t ha−1at an arugula density of 400,000 plants ha−1.